Theologizing “Teing Hang” Ceremony In The Culture of Manggarai, Indonesia - Gregorius Pasi (Asosiasi Ahli Filsafat Keilahian Indonesia, 2021)
The Teing Hang ceremony, which is practised by the Manggarai people in East Nusa Tenggara, Indonesia, celebrates local wisdom regarding the relationality of the Manggarai people with the Highest Being, with one’s fellow beings who are still living and with the relatives who have died. The methodology is what I call “critical reading” of the dialectical model, which has been proposed by Stefan Bevans and Daniel Pilario. By using the critical reading method of the teing hang ceremony data (collected through interviews and reviews of related studies), I found that the local wisdom of Manggarai can explain and illuminate the content of the Catholic faith with regard to the communion of saints in three ways. First, the communion of saints is a participation in God's providence. Second, the communion of saints is a participation in the lives of one’s fellow beings. Third, the communion of saints is an intersubjectivity relationship between those who believe in Christ and are indwelt by His Spirit.